Utilization of a Mobile Multifunctional Workstation for Coronavirus Nasopharyngeal/Oropharyngeal Specimen Collection - Xiaojing Lian; Lili Zhang; Yang Zhao; Yuhua Li; Xuemin Jing; Xin Liu; Jianing Han; Jianhong Ma; Yongyong Zhang; Huimin Guo; Xiaojie Huang (Frontiers Media S.A., 2022)
ObjectivesThis study aimed to explore the utilization of a mobile multifunctional workstation for COVID-19 sample collection.MethodsTwenty-four nurses and 150 individuals who took nucleic acid tests using mobile multifunctional workstations in Beijing Youan Hospital, Capital Medical University, from September to November 2020, were enrolled in the study as the observation group. As the control group, we included 36 nurses and 150 individuals who did not use the workstations from June to September 2020. We compared the two groups on (1) comfort of working environment, self-perceived security, the convenience of information system, operational process flexibility, pharyngeal acquisition visibility, and effectiveness of communication among nurses; and (2) self-perceived safety, waiting time, and overall satisfaction among individuals who took nucleic acid tests.ResultsThe satisfaction score of nurses in the observation group of nurses were significantly higher than those of the control group (OR = 17.297 95% CI:4.294, 69.673), as well as the convenience of the information system (OR = 6.250 95% CI: 1.775, 22.008), and communication effectiveness (OR = 5.588 95% CI: 1.590, 19.646). Among individuals who took nucleic acid tests, the overall satisfaction (P < 0.05) and self-perceived security (P < 0.05) had statistical differences between the observation group and the control group.ConclusionsThe mobile multifunctional workstation for specimen collection could improve the comfort of the working environment, the convenience of information systems, and the effectiveness of communication among nurses.It can improve satisfaction and self-perceived security among people who took nucleic acid tests.